Heat Transport Efficiency of Magnetized AA7072/H2O Nanofluid and AA7072 + AA7075/H2O Hybrid Nanofluid Past a Non-Linear Porous Stretching Sheet - Marayanagaraj, Shanmugapriya; Raman, Sundareswaran; Alameri, Abdu (AMG Transcend Association, 2024)
The next-generation thermal fluid, that is, the hybrid nanofluids (hbnfs) are extensively used in numerous fields like industrial and manufacturing sectors as well as recent developments in biotechnology. Inspired by these applications, we investigated the argumentation of thermal energy transfer of AA7072 and AA7072 + AA7075 alloy nanoparticles (nps) suspended in H_2 O - based nanofluid and hybrid nanofluid flow past a non-linear porous stretching sheet. Thermal radiation, viscous dissipation, and heat source/sink are also studied in the modeling. The modeling PDEs are transmuted into ODEs by opting for appropriate similarity transformations. Furthermore, the transmuted equations are solved numerically in MATLAB using Runge-Kutta-Fehlbergs fourth-fifth order (RKF-45) technique by adopting the shooting method. The graphical representation is accomplished for important physical factors to check the behaviors of flow profiles. The velocity profile for AA7072 + AA7075/ H_2 O is higher than AA7072/ H_2 O. By increasing magnetic field parameter M and permeability parameter K_1, the velocity component (f^' (?)), gain diminished trend for both AA7072/ H_2 O and AA7072 + AA7075/ H_2 O. The influence of Eckert number (Ec), and Heat source and sink parameter (Q) displays the rising trend in temperature profile for both nano and hybrid nanofluid. But the hybrid nanofluid is more effective when equated with nanofluid for both Ec, and Q. Moreover, the Dragging friction (Df), and Nusselt number (Nn) are also evaluated.